Advancements In CRISPR-CAS9: A New Era for Genome Editing in Gene Therapy and Stem Cell Applications - Bangash, Sudhair Abbas; Naouss, Bilal Abdul Kader; Muhammad Ali, Shehryar; Alavi, Amina Farrukh (Journal of Neonatal Surgery, 2025)
Purpose: This study explores the advancements in CRISPR-Cas9 technology and its potential to revolutionize gene therapy and stem cell applications. It aims to assess the level of public awareness, the perceptions surrounding its effectiveness in treating genetic disorders, ethical implications, and its promise in stem cell research. Aim: The primary objective of this paper is to evaluate the role of CRISPR-Cas9 in gene therapy for genetic disorders and its application in advancing stem cell therapies. Additionally, the study seeks to identify the ethical concerns and future outlook of CRISPR-Cas9 from a diverse group of participants with varying levels of expertise and familiarity with the technology. Approach: A mixed-methods survey was employed to collect both quantitative and qualitative data from 130 participants, including researchers, healthcare professionals, and the general public. The questionnaire consisted of sections covering demographic data, awareness of CRISPR-Cas9, its potential in gene therapy, ethical considerations, and its role in stem cell research. Methods: The survey included Likert-scale questions to quantify participant attitudes and opinions on the effectiveness, ethical concerns, and future of CRISPR-Cas9, alongside open-ended questions for qualitative feedback. Data was analyzed using descriptive statistics for quantitative data and thematic analysis for qualitative responses. Results: The findings revealed strong confidence in CRISPR-Cas9's potential to treat genetic disorders, with over 70% of participants expressing optimism about its effectiveness. While a significant proportion of participants showed support for CRISPR-Cas9’s role in stem cell therapies, there were notable ethical concerns, particularly regarding its use in human gene editing and "designer babies." Findings: The study identified key areas of public interest, including the effectiveness of CRISPR-Cas9 in genetic disease treatment, its ethical implications, and its transformative potential for regenerative medicine and stem cell applications. Despite these positive responses, concerns about the regulation and ethical governance of CRISPR-Cas9 remain critical. Theoretical Implications: This paper provides insight into the societal perception of CRISPR-Cas9, contributing to the theoretical understanding of how advanced gene editing technologies are viewed across different sectors. The findings underline the need for comprehensive regulatory frameworks to address ethical concerns and ensure the responsible application of CRISPR-Cas9 in medical treatments. Practical Implications: The results of this study have practical implications for the future of gene therapy and stem cell research. It highlights the necessity for greater public education on CRISPR-Cas9 and the importance of developing ethical guidelines to govern its use in human genetic modification. Originality/Value: This paper offers a comprehensive overview of public perceptions of CRISPR-Cas9, blending both scientific and societal perspectives. It contributes to the growing body of knowledge on the ethical, scientific, and societal implications of gene editing technologies and serves as a foundation for future research and policy development in this field